Oral Manifestation of Autoimmune Systemic Disorder: A Case Report - Divya Jyoti; Chitrita G Mukherjee; Jeevendra N Shukla; Aparna Singh; Swati Sagar (Journal of South Asian Association of Pediatric Dentistry)
Celiac disease is an autoimmune disorder that occurs in genetically predisposed people caused by gluten which attacks the lining of the small intestines and damages the villi, leading to malabsorption. Sometimes recurrent aphthous ulcers and benign migratory glossitis could be the only oral manifestation of this disorder. When pediatric dentists encounter these features, they should enquire about other symptoms, associated with celiac disease. In suspected cases, appropriate referral and a timely diagnosis can help prevent complications of this disorder.